KEBEBASAN TOKOH PEREMPUAN DALAM NOVEL PADA SEBUAH KAPAL KARYA N.H. DINI: KAJIAN FEMINISME - Nensilianti, Nensilianti; Ridwan, Ridwan; Shalsabilah Z, Shafira (Universitas Hamzanwadi, 2024)
Women are complex creatures with diverse lives, thus giving rise to a continuous and broad discourse on women's studies. Various approaches are taken to achieve women's liberation, and one of these approaches is the use of literary works. This article aims to examine women's freedom in the novel